2014
DOI: 10.1007/978-1-4939-1743-3_13
|View full text |Cite
|
Sign up to set email alerts
|

Detection and Characterization of Mycoviruses in Arbuscular Mycorrhizal Fungi by Deep-Sequencing

Abstract: Fungal viruses (mycoviruses) often have a significant impact not only on phenotypic expression of the host fungus but also on higher order biological interactions, e.g., conferring plant stress tolerance via an endophytic host fungus. Arbuscular mycorrhizal (AM) fungi in the phylum Glomeromycota associate with most land plants and supply mineral nutrients to the host plants. So far, little information about mycoviruses has been obtained in the fungi due to their obligate biotrophic nature. Here we provide a te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…Pioneering studies indicate that AMF endobacteria may improve the fungal ecological fitness (Salvioli et al, 2016) and promote antioxidative responses in both fungal and plant hosts (Vannini et al, 2016). However, data on the impact of endobacteria and mycoviruses (Ezawa et al, 2015) on AMF phenotypic expression and higher order biological interactions are scarce and deserve further investigations.…”
Section: Introductionmentioning
confidence: 99%
“…Pioneering studies indicate that AMF endobacteria may improve the fungal ecological fitness (Salvioli et al, 2016) and promote antioxidative responses in both fungal and plant hosts (Vannini et al, 2016). However, data on the impact of endobacteria and mycoviruses (Ezawa et al, 2015) on AMF phenotypic expression and higher order biological interactions are scarce and deserve further investigations.…”
Section: Introductionmentioning
confidence: 99%
“…Their research led to the discovery of novel mycoviruses, never previously found in fungi, that belonged to the families Benyviridae, Ophioviridae , and Virgaviridae (Marzano et al, 2016 ); and Khalifa et al ( 2016 ) who discovered 10 viruses in five S. sclerotiorum strains using Illumina sequencing (Khalifa et al, 2016 ), and Osaki et al ( 2016 ), using deep sequencing, found that 17 mycoviruses co-infected a strain of Fusarium poae . Mycoviruses were found on the soybean phyllosphere and in the roots colonized by arbuscular mycorrhizal fungi (Ezawa et al, 2015 ; Marzano and Domier, 2016 ). Australia and New Zealand are geographically embraced by oceans as a natural barrier to spread of pathogens, unlike in New Zealand, whether viruses that infect S. sclerotiorum are present in Australia has never been determined.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, when high-throughput sequencing is used for virus detection, the enrichment step, which might bias detection, is not necessary. High-throughput sequencing was used to detect mycoviruses on the phyllosphere and the arbuscular mycorrhizal fungi colonized in the roots (Ezawa et al, 2015 ; Marzano and Domier, 2016 ). By deep sequencing extracted dsRNAs, different mycoviral species were shown to coinfect a Fusarium poae fungal strain (Osaki et al, 2016 ), as illustrated in other fungi, such as Rhizoctonia solani (Bartholomäus et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%